Tuberculosis elimination: where are we now? - Matteelli, Alberto; Rendon, Adrian; Tiberi, Simon; Al-Abri, Seif; Voniatis, Constantia; Carvalho, Anna Cristina C.; Centis, Rosella; D'Ambrosio, Lia; Visca, Dina; Spanevello, Antonio; Battista Migliori, Giovanni (European respiratory review, 2018)
Tuberculosis (TB) still represents a major public health issue in spite of the significant impact of the efforts made by the World Health Organization (WHO) and partners to improve its control. In 2014 WHO launched a new global strategy (End TB) with a vision of a world free of TB, and a 2035 goal of TB elimination (defined as less than one incident case per million). The aim of this article is to summarise the theoretical bases of the End TB Strategy and to analyse progresses and persistent obstacles on the way to TB elimination. The evolution of the WHO recommended strategies of TB control (Directly Observed Therapy, Short Course (DOTS), Stop TB and End TB) are described and the concept of TB elimination is discussed. Furthermore, the eight core activities recently proposed by WHO as the milestones to achieve TB elimination are discussed in detail. Finally, the recently published experiences of Cyprus and Oman on their way towards TB elimination are described, together with the regional experience of Latin America. New prevention, diagnostic and treatment tools are also necessary to increase the speed of the present TB incidence decline.